2016
DOI: 10.2500/aap.2016.37.3953
|View full text |Cite
|
Sign up to set email alerts
|

Serum clusterin level in children with atopic dermatitis

Abstract: The serum clusterin level was higher in children with AD than in the healthy control group and increased with the severity of AD. Serum clusterin may be a candidate molecule that reflects AD and its severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 1 publication
0
8
0
Order By: Relevance
“…In detail, four studies were published in the 1990s, nine in the 2000s, and 21 in the last decade. Different geographical areas (and ethnicities) were not uniformly represented: 16 studies [17,18,23,24,27,[32][33][34][35][36][37][38]40,42,45,46] were performed in Eastern Asia (8 in Japan, 6 in Korea, 2 in Taiwan), nine [21,28,31,39,41,43,44,47,48] in Europe (3 in Russia, 2 in Germany, 1 in Finland, Italy, Norway, Switzerland), four [20,22,29,30] in Middle Eastern countries (3 in Turkey, 1 in Israel), two [25,26] in Southern Asia (Bangladesh, India), and one [49] in the United States of America. Another study [19] included patients from multiple Canadian and European centers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In detail, four studies were published in the 1990s, nine in the 2000s, and 21 in the last decade. Different geographical areas (and ethnicities) were not uniformly represented: 16 studies [17,18,23,24,27,[32][33][34][35][36][37][38]40,42,45,46] were performed in Eastern Asia (8 in Japan, 6 in Korea, 2 in Taiwan), nine [21,28,31,39,41,43,44,47,48] in Europe (3 in Russia, 2 in Germany, 1 in Finland, Italy, Norway, Switzerland), four [20,22,29,30] in Middle Eastern countries (3 in Turkey, 1 in Israel), two [25,26] in Southern Asia (Bangladesh, India), and one [49] in the United States of America. Another study [19] included patients from multiple Canadian and European centers.…”
Section: Resultsmentioning
confidence: 99%
“…Another study [19] included patients from multiple Canadian and European centers. Sample sizes were often small: ten papers [18,21,29,31,33,35,44,46,48,49] reported data concerning a population of less than 20 AD patients, eight papers [26,28,36,37,39,42,45,47] examined 20 to 40 patients, and only in seven cases [19,23,24,32,34,38,41,43] the number of patients was 100 or more. AD patients were adults (age >18 years) in seven studies, children in 19 (in four cases, patients were of neonatal age), both adults and children in eight.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Various cellular stress stimuli have been shown to regulate transcriptional activity of AP-1 [223]. Differential CLU expression was similarly observed in other oxidative stressrelated pathologies including asthma [224], atopic dermatitis [225], diabetes type 2 [226], coronary heart disease [226], and cancer [227]. Oxidative stress increases CLU expression.…”
Section: Clusterinmentioning
confidence: 91%
“…In transitioning to atopic dermatitis, Sol et al 13 investigated serum levels of clusterin, a small heat shock protein associated with the clearance of cellular debris and apoptosis, as a potential predictive biomarker of the disease in 140 children with atopic dermatitis. Their findings indicated that serum clusterin may be a candidate molecule that reflects the severity of the disease.…”
mentioning
confidence: 99%